Pengaruh Pendapatan Biaya Komisi Provisi Dan Vakuta Asing Pada Return On Aset (ROA) Pada Bank Mauamalat Priode 2015-2022 - Pipin Pipin; Tria Noviyanti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The purpose of this study was to examine the effect of fee-based income and foreign exchange fees on return on assets at Muamalat bank for the 2015-2020 period. There are two types of fee-based income studied, namely fee and commission income, and foreign exchange transaction service income. The sample is using Quarterly financial reports for the 2015-2020 period in this study. Multiple regression based on ordinary least squares (OLS). The results showed that the three types of fee-based income had a positive and significant effect on return on assets. However, total assets have no significant effect. Overall, the results suggest that banks should increase their fee-based income activities to improve profitability.